Complete chloroplast genome sequence of Populus euphratica from PacBio Sequel platform. Issue 2 (1st February 2021) - Jiang, Zhen-Bo; Zhai, Jun-Tuan; Jiao, Pei-Pei; Yang, Tian-Ge; Wu, Zhi-Hua; Li, Zhi-Jun
Abstract: Populus euphratica Oliv., one of tall arbors growing in desert areas, has great stress resistance. The complete chloroplast genome was reported in this study using the PacBio Sequel Platform. The chloroplast genome with a total size of 157, 881 bp consisted of two inverted repeats (IRs) (27, 666 bp) separated by a large single-copy region (85, 906 bp) and a small single-copy region (16, 643 bp). Further annotation revealed the chloroplast genome contains 111 genes, including 77 protein-coding genes, 30 tRNA genes, and four rRNA genes. The information of the chloroplast genome will be useful for study on the evolution of P. euphratica in the future.